2021
DOI: 10.3389/fimmu.2021.702037
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation-Based Interferon Scores Associate With Sub-Phenotypes in Primary Sjögren’s Syndrome

Abstract: Primary Sjögren’s syndrome (pSS) is an autoimmune inflammatory disease with profound clinical heterogeneity, where excessive activation of the type I interferon (IFN) system is considered one of the key mechanisms in disease pathogenesis. Here we present a DNA methylation-based IFN system activation score (DNAm IFN score) and investigate its potential associations with sub-phenotypes of pSS. The study comprised 100 Swedish patients with pSS and 587 Swedish controls. For replication, 48 patients with pSS from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Studies showed that IFIT1 and IFI44L were associated with the overactivation of the type I IFN in pSS, which was of great value in guiding treatment decisions, monitoring and patient strati cation [14,15]. As the ligand of chemokine receptor CXCR3, CXCL9 was induced by IFN γ and mainly acted on monocytes/macrophages and lymphocytes, mediating in ammatory responses [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that IFIT1 and IFI44L were associated with the overactivation of the type I IFN in pSS, which was of great value in guiding treatment decisions, monitoring and patient strati cation [14,15]. As the ligand of chemokine receptor CXCR3, CXCL9 was induced by IFN γ and mainly acted on monocytes/macrophages and lymphocytes, mediating in ammatory responses [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation‐based IFN scores associate with sub‐phenotypes in primary Sjögren's syndrome 46 . The DNA methylation‐based IFN score is thus a promising alternative to mRNA‐based scores for identification of patients with activation of the IFN system and may be applied for patient stratification guiding treatment decisions, monitoring, and inclusion in clinical trials 46 …”
Section: Focal Inflammation With Mixed Cellular Compositionmentioning
confidence: 99%
“…45 DNA methylation-based IFN scores associate with subphenotypes in primary Sjögren's syndrome. 46 The DNA methylation-based IFN score is thus a promising alternative to mRNA-based scores for identification of patients with activation of the IFN system and may be applied for patient stratification guiding treatment decisions, monitoring, and inclusion in clinical trials. 46 As already alluded to, a minor salivary gland biopsy with focal lymphocytic sialadenitis and a focus score of ≥1 is the currently accepted pathological finding confirming the exocrinopathy of Sjögren's syndrome.…”
Section: With Mixed Cellular Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation is a well-studied epigenetic modi cations that regulates gene expression 8 . So far, a number of studies have provided evidence of aberrant DNA methylation pro les in rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and sjogren's syndrome (SS) patients 9,10,11,12,13,14,15,16,17,18 . The DNA methylation changes in IgG4-RD patients are poorly understood.…”
Section: Introductionmentioning
confidence: 99%